Changes in plasma fatty acid composition are associated with improvements in obesity and related metabolic disorders: A therapeutic approach to overweight adolescents. Issue 1 (February 2018) - Guerendiain, Marcela; Montes, Rosa; López-Belmonte, Gemma; Martín-Matillas, Miguel; Castellote, Ana I.; Martín-Bautista, Elena; Martí, Amelia; Martínez, J. Alfredo; Moreno, Luis; Garagorri, Jesús Mª; Wärnberg, Julia; Caballero, Javier; et al.
Summary: Background & aims: In recent years, obesity has reached alarming levels among children and adolescents. The study of plasma fatty acid (FA) composition, as a reflection of diet, and its associations with other parameters, that are closely linked to obesity and the cardiometabolic profile, may be useful for setting nutritional goals for obesity treatment and prevention. This study explored the relationship between plasma FA levels and body fat and cardiometabolic risk markers, in overweight adolescents. Methods: A multidisciplinary weight loss program was followed by 127 overweight and obese adolescents aged 12–17 years old. Plasma FA composition, anthropometric indicators of adiposity and biochemical parameters were analyzed at baseline, two months (the end of the intensive intervention phase) and six months (the end of the extensive phase). Results: While saturated fatty acid (SFA) and n-6 polyunsaturated fatty acid (PUFA) levels decreased significantly during the intervention, monounsaturated fatty acid (MUFA) and n-3 PUFA showed the opposite trend. The decrease in SFA C14:0 was associated with a reduction in total and LDL cholesterol, apolipoprotein B and insulin. The increase in MUFAs, especially C18:1n-9, was related to a reduction in weight, fat mass, fat mass index and glucose. Regarding PUFAs, changes in the n-3 series were not associated with any of the parameters studied, whereas the reduction in n-6 PUFAs was directly related to weight, fat mass, total and HDL cholesterol, apolipoprotein A1, glucose and insulin, and inversely associated with diastolic blood pressure. The adolescents with greater weight loss presented significant changes in MUFAs, n-6 PUFAs and C14:0. Conclusions: Modifications in plasma FA composition were associated with adiposity reduction and cardiometabolic profile improvement in an anti-obesity program aimed at adolescents. The changes observed in FA composition were related to the success of the treatment, since the individuals most affected by these variations were those who presented the greatest weight loss.